Gene Expression and Apoptosis Levels in Cumulus Cells of Patients with Polymorphisms of FSHR and LHB Undergoing in Vitro Fertilization Program - Liana Bosco; Giovanni Ruvolo; Claudio Luparello; Stefania Ferrari; Domenico Valerio; Daniele Santi; Paola Piomboni; Elena Sarcina; Monica Lispi; Maria Carmela Roccheri (Cellular Physiology and Biochemistry, 2017)
Background/Aims: FSH receptor (FSHR) Ala307Thr and Asn680Ser and LHβ chain (LHB) Trp28Arg and Ile35Thr polymorphisms affect the response to pharmacological ovarian stimulation with r-FSH in women undergoing assisted reproductive treatment (ART). Here, we evaluated the expression level of selected genes involved in follicle maturation and the possible onset of apoptosis in cumulus cells of patients with single and double FSHR and LHB polymorphisms, as potential markers of oocyte competence. Methods: Cumulus cells from 36 stimulated patients were collected and SNP genotyping performed by PCR. Gene expression was evaluated through real-time PCR, and apoptosis estimated via TUNEL assay, and cleaved caspase-3 and pAKT immunostaining. Results: The cumulative data show significant correlations indicating that the genetic alteration of FSHR and/or LHB genes may lead to perturbations of the signaling network programmed to granulosa cell survival and follicle development. Notably, when double heterozygotes were compared to the rest of the patients, a higher level of apoptosis in terms of both DNA fragmentation index and amount of active caspase-3 was observed in cumulus cells. Conclusions: These results may help to define personalized stimulation protocols in ART programs, to increase the success rate of ICSI procedures in accordance with the polymorphic condition of the individual patient.